Trust in machines: how personality trait shapes static and dynamic trust across different human–machine interaction modalities - Zhu, Yi; Hua, Guiqi; Liu, Xinning; Wang, Chang; Tang, Mingwei (Frontiers in Psychology, 2025)
With the rapid advancement of Artificial Intelligence (AI), intelligent machines are increasingly displaying “human-like personality,” shifting Human–Machine Interaction (HMI) from one-way guidance to interactive, multi-level dynamics. Trust plays a pivotal role in the development and maintenance of these evolving interactions. While personality traits have been recognized as key factors in shaping and enhancing interpersonal trust, their role in the development of static and dynamic trust in HMI remains underexplored. This study investigates how personality traits influence trust in HMI across two interaction modalities: Personal Computer (PC) and Virtual Reality (VR). By simulating real-world interaction scenarios, we examined the impact of personality traits on both static and dynamic trust, and explored the relationship between them. The results showed that in the PC modality, personality traits significantly affected both static and dynamic trust, with static trust serving as a strong predictor of dynamic trust. In the VR modality, personality traits significantly influenced static trust, and static trust again played a key role in shaping dynamic trust. These findings underscore the foundational importance of static trust in the evolution of trust in HMI, and highlight the need to consider individual personality differences and interaction modalities in the design of AI-driven interfaces to foster trust and promote long-term engagement.